2008
DOI: 10.1093/eurheartj/ehn302
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial linear lesions are required for successful treatment of persistent atrial fibrillation

Abstract: Although persistent AF can be terminated by catheter ablation without linear lesions, the majority will require linear lesions for macro re-entrant AT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
217
1
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(230 citation statements)
references
References 44 publications
7
217
1
5
Order By: Relevance
“…Namely, postprocedural rate of atrial tachycardia was 2-2.5 times higher among patients with incomplete linear lesions [202].…”
Section: Phrenic Nerve Injurymentioning
confidence: 89%
“…Namely, postprocedural rate of atrial tachycardia was 2-2.5 times higher among patients with incomplete linear lesions [202].…”
Section: Phrenic Nerve Injurymentioning
confidence: 89%
“…In recurrent AFparox ectopic focal activity is thought to be local and limited to one or a few sites. On the contrary in AFpers there tend to be multiple ectopic sites throughout the atria and advanced damage of atrial myocardium (more susceptible substrate) [10][11][12][13]. Large left atrial (LA) size was found to be a predictor of recurrence of AF after electrical or pharmacological cardio-version as well as after ablative treatment [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…These approaches included ablation of complex-fractionated atrial electrograms (CFAe), targeting local cycle length (frequency) gradients, linear ablation between fixed anatomical structures, isolation of the superior vena cava, ablation of the coronary sinus or ligament of Marshall, electrical isolation of the left atrial appendage, targeting ganglionated plexi, or a combination of these approaches as in the step-wise ablation approach. [21][22][23][24][25][26][27][28] end points of these ablation strategies can be variable. When an anatomic ablation strategy such as linear ablation and isolation of other thoracic veins is pursued, termination often is not sought after as a procedural end point.…”
Section: Catheter Ablationmentioning
confidence: 99%